"Os Limites? Que Limites?" - Neves, Eduarda (2013)
From the illusion of the similitude of reality to the illusion of the representation of identity. The unsolvable tension between reference and representation. Self-portrait, identity and machine of capitalist de-territorialisation. Technically speaking, what is left of the subject? Limits? What limits?